Case Report: Response of cutaneous lupus lesions in SLE to interferon receptor blockade parallels reduction of interferon score in blood - Günther, Claudia; Wolf, Christine; Fennen, Louisa; Rösing, Sarah; Beissert, Stefan; Aringer, Martin; Lee-Kirsch, Min Ae (Frontiers in Immunology, 2023)
Cutaneous lupus erythematosus (CLE), the main manifestation of systemic lupus erythematosus (SLE), is driven by type I interferons (IFN) and often only partially responds to conventional therapies. Treatment of 7 SLE patients with the monoclonal antibody anifrolumab induced fast and sustained remission of previously refractory CLE lesions, beginning within the first weeks of treatment. Decline in CLASI-A score was paralleled by a reduction in IFN score determined by mRNA expression of 7 IFNstimulated genes (ISG) in blood. These data suggest that a subset of ISG could be a valuable biomarker in CLE.